Personality Emoji Scale: Validity and Reliability Evidences - Cardoso Rezende, Maria Thalita (2025)
Objective. To present evidence of validity and reliability of the Emoji Personality Scale, considering that this may be a dynamic and little explored strategy for measuring individual differences. The scale uses different emojis to illustrate characteristics of the Big Five. In addition, this measure’s relationship with sociodemographic variables was also investigated. Method. 234 individuals participated, with a mean age of 20.5 years (SD = 5.60). Results. Model-fit indicators were observed for the five-factor model. Reliability ranged from .61 to .89, with gender differences observed in agreeableness and extraversion. Finally, correlations with another personality measure were observed.